18
$\begingroup$

It is known that the transformation rule when you change coordinate frames of the Christoffel symbol is:

$$ \tilde \Gamma^{\mu}_{\nu\kappa} = {\partial \tilde x^\mu \over \partial x^\alpha} \left [ \Gamma^\alpha_{\beta \gamma}{\partial x^\beta \over \partial \tilde x^\nu}{\partial x^\gamma \over \partial \tilde x^\kappa} + {\partial ^2 x^\alpha \over \partial \tilde x^\nu \partial \tilde x^\kappa} \right ]$$

Is there any way to prove this rule using only the definition of the Christoffel via the metric tensor? That is, using:

$$ \Gamma^\mu _{\nu\kappa} = \frac{1}{2}g^{\mu\lambda}\left(g_{\lambda\kappa,\nu}+g_{\nu\lambda,\kappa}-g_{\nu\kappa,\lambda} \right)$$

All proofs have I've seen of the transformation law involve another method.

$\endgroup$
15
$\begingroup$

This is very straightforward, just substitute the transformation rules and collect the terms.

Here are some details.

The inverse metric transforms, as we know, by the rule: $$ g^{\mu \lambda} = \frac{\partial{\bar{x}}^\mu}{\partial{x}^\alpha} \frac{\partial{\bar{x}}^\lambda}{\partial{x}^\delta} g^{\alpha \delta} $$

The partial derivatives need some calculations that can be presented as $$ \begin{align*} g_{\lambda \kappa , \nu} & = \frac{\partial}{\partial{\bar{x}^\nu}} \Big( \frac{\partial{x^\delta}}{\partial{\bar{x}^\lambda}} \frac{\partial{x^\gamma}}{\partial{\bar{x}^\kappa}} g_{\delta \gamma} \Big) \\ &= \frac{\partial{x^\delta}}{\partial{\bar{x}^\lambda}} \frac{\partial{x^\gamma}}{\partial{\bar{x}^\kappa}} \frac{\partial{x^\beta}}{\partial{\bar{x}^\nu}} g_{\delta \gamma , \beta} + g_{\delta \gamma} \frac{\partial}{\partial{\bar{x}^\nu}} \Big( \frac{\partial{x^\delta}}{\partial{\bar{x}^\lambda}} \frac{\partial{x^\gamma}}{\partial{\bar{x}^\kappa}} \Big) \end{align*} $$

Similarly, $$ g_{\nu \lambda , \kappa} = \frac{\partial{x^\beta}}{\partial{\bar{x}^\nu}} \frac{\partial{x^\delta}}{\partial{\bar{x}^\lambda}} \frac{\partial{x^\gamma}}{\partial{\bar{x}^\kappa}} g_{\beta \delta , \gamma} + g_{\beta \delta} \frac{\partial}{\partial{\bar{x}^\kappa}} \Big( \frac{\partial{x^\beta}}{\partial{\bar{x}^\nu}} \frac{\partial{x^\delta}}{\partial{\bar{x}^\lambda}} \Big) $$ and $$ g_{\nu \kappa , \lambda} = \frac{\partial{x^\beta}}{\partial{\bar{x}^\nu}} \frac{\partial{x^\gamma}}{\partial{\bar{x}^\kappa}} \frac{\partial{x^\delta}}{\partial{\bar{x}^\lambda}} g_{\beta \gamma , \delta} + g_{\beta \gamma} \frac{\partial}{\partial{\bar{x}^\lambda}} \Big( \frac{\partial{x^\beta}}{\partial{\bar{x}^\nu}} \frac{\partial{x^\gamma}}{\partial{\bar{x}^\kappa}} \Big) $$

Substituting these identities into your "definition" $$ \Gamma^\mu _{\nu\kappa} = \frac{1}{2}g^{\mu\lambda}\left(g_{\lambda\kappa,\nu}+g_{\nu\lambda,\kappa}-g_{\nu\kappa,\lambda} \right) $$ and taking into account that $$ \Gamma^\alpha _{\beta \gamma} = \frac{1}{2}g^{\alpha \delta}\left(g_{\delta \gamma , \beta}+g_{\beta \delta , \gamma} - g_{\beta \gamma , \delta} \right) $$ it is not difficult now to show the required transformation rule for the Christoffel symbols.

$\endgroup$
0
$\begingroup$

Let $(U, x^1, \ldots, x^n)$ be a chart of Riemannian manifold $M$, smooth coordinate chang $(U, g_{\mu\nu}, x^1, \ldots, x^n) \to (U, g'_{\mu'\nu'}, y^1, \ldots, y^n)$. Then $\partial^x_\mu =\frac{\partial}{\partial x^\mu} = \frac{\partial y ^ {\mu'}}{\partial x^\mu} \frac{\partial}{\partial y^{\mu'}} = \frac{\partial y ^ {\mu'}}{\partial x^\mu} \partial^y_{\mu'}$, $\partial^x_\nu = \frac{\partial y ^ {\nu'}}{\partial x^\nu} \partial^y_{\nu'}$.

Inner product is invariant under coordinate change.

For $v, w\in T_p U, v = v^\mu \partial^x_\mu = v^\mu \frac{\partial y ^ {\mu'}}{\partial x^\mu} \partial^y_{\mu'}, w = w^\nu \partial^x_\nu = w^\nu \frac{\partial y ^ {\nu'}}{\partial x^\nu} \partial^y_{\nu'}$.

$\langle v, w\rangle = g_{\mu\nu}v^\mu w^\nu = g'_{\mu'\nu'}\frac{\partial y ^ {\mu'}}{\partial x^\mu}\frac{\partial y ^ {\nu'}}{\partial x^\nu} v^\mu w^\nu $, thus $g'_{\mu'\nu'} = \frac{\partial x^\mu}{\partial y ^ {\mu'}} \frac{\partial x^\nu}{\partial y ^ {\nu'}}g_{\mu\nu}$. $g$ is a tensor.

$\Gamma_{\mu \nu}^{\lambda}=\frac{1}{2} g^{\lambda \rho}(\partial_{\mu}g_{\nu \rho} +\partial_{\nu}g_{\rho \mu}-\partial_{\rho}g_{\mu \nu}), {\Gamma'}_{\mu' \nu'}^{\lambda'}=\frac{1}{2} {g'}^{\lambda' \rho'}(\partial_{\mu'} {g'}_{\nu' \rho'} +\partial_{\nu'} {g'}_{\rho' \mu'}-\partial_{\rho'}{g'}_{\mu' \nu'})$.

$\partial_{\alpha '}g_{\beta ' \gamma '}' =\frac{\partial x^{\alpha } }{\partial y^{\alpha '} }\frac{\partial x^{\beta } }{\partial y^{\beta '} }\frac{\partial x^{\gamma } }{\partial y^{\gamma'}} \partial_\alpha g_{\beta \gamma} + g_{\beta \gamma} (\frac{\partial x^{\gamma} }{\partial y^{\gamma'} }\frac{\partial^{2} x^{\beta } }{\partial y^{\alpha '}\partial y^{\beta '} }+ \frac{\partial x^{\gamma } }{\partial y^{\beta '} }\frac{\partial^{2} x^{\beta } }{\partial y^{\alpha '}\partial y^{\gamma '}})$ \begin{align}\notag &\partial_{\mu'} {g'}_{\nu' \rho'} + \partial_{\nu'} {g'}_{\rho' \mu'}-\partial_{\rho'}{g'}_{\mu' \nu'}\\ \notag&=\frac{\partial x^{\mu } }{\partial y^{\mu'} }\frac{\partial x^{\nu } }{\partial y^{\nu '} }\frac{\partial x^{\rho } }{\partial y^{\rho'}} \partial_\mu g_{\nu \rho} + g_{\nu \rho} (\frac{\partial x^{\rho} }{\partial y^{\rho'} }\frac{\partial^{2} x^{\nu } }{\partial y^{\mu '}\partial y^{\nu '} }+ \frac{\partial x^{\rho } }{\partial y^{\nu '} }\frac{\partial^{2} x^{\nu } }{\partial y^{\mu '}\partial y^{\rho '}})\\ \notag&+ \frac{\partial x^{\nu } }{\partial y^{\nu '} }\frac{\partial x^{\rho } }{\partial y^{\rho '} }\frac{\partial x^{\mu } }{\partial y^{\mu'}} \partial_\nu g_{\rho \mu} + g_{\rho \mu} (\frac{\partial x^{\mu} }{\partial y^{\mu'} }\frac{\partial^{2} x^{\rho } }{\partial y^{\nu '}\partial y^{\rho '} }+ \frac{\partial x^{\mu} }{\partial y^{\rho '} }\frac{\partial^{2} x^{\rho } }{\partial y^{\nu '}\partial y^{\mu '}})\\ \notag&-\frac{\partial x^{\rho } }{\partial y^{\rho '} }\frac{\partial x^{\mu } }{\partial y^{\mu '} }\frac{\partial x^{\nu } }{\partial y^{\nu'}} \partial_\rho g_{\mu \nu} - g_{\mu\nu} (\frac{\partial x^{\nu} }{\partial y^{\nu'} }\frac{\partial^{2} x^{\mu } }{\partial y^{\rho'}\partial y^{\mu'} }+ \frac{\partial x^{\nu} }{\partial y^{\mu'} }\frac{\partial^{2} x^{\mu} }{\partial y^{\rho '}\partial y^{\nu'}})\\ \notag&=\frac{\partial x^{\mu } }{\partial y^{\mu'} }\frac{\partial x^{\nu } }{\partial y^{\nu '} }\frac{\partial x^{\rho } }{\partial y^{\rho'}}(\partial_\mu g_{\nu \rho}+\partial_\nu g_{\rho \mu}-\partial_\rho g_{\mu \nu})+g_{\nu \rho} (\frac{\partial x^{\rho} }{\partial y^{\rho'} }\frac{\partial^{2} x^{\nu } }{\partial y^{\mu '}\partial y^{\nu '} }+ \frac{\partial x^{\rho } }{\partial y^{\nu '} }\frac{\partial^{2} x^{\nu } }{\partial y^{\mu '}\partial y^{\rho '}}\\ \notag&\quad+\frac{\partial x^{\rho} }{\partial y^{\mu'} }\frac{\partial^{2} x^{\nu } }{\partial y^{\nu '}\partial y^{\rho '} }+ \frac{\partial x^{\rho} }{\partial y^{\rho '} }\frac{\partial^{2} x^{\nu } }{\partial y^{\nu '}\partial y^{\mu '}} -\frac{\partial x^{\rho} }{\partial y^{\nu'} }\frac{\partial^{2} x^{\nu } }{\partial y^{\rho'}\partial y^{\mu'} }- \frac{\partial x^{\rho} }{\partial y^{\mu'} }\frac{\partial^{2} x^{\nu} }{\partial y^{\rho '}\partial y^{\nu'}})\\ \notag&=\frac{\partial x^{\mu } }{\partial y^{\mu'} }\frac{\partial x^{\nu } }{\partial y^{\nu '} }\frac{\partial x^{\rho } }{\partial y^{\rho'}}(\partial_\mu g_{\nu \rho}+\partial_\nu g_{\rho \mu}-\partial_\rho g_{\mu \nu}) +2 g_{\nu \rho} \frac{\partial x^{\rho} }{\partial y^{\rho'} }\frac{\partial^{2} x^{\nu } }{\partial y^{\mu '}\partial y^{\nu '} } \end{align} \begin{align}\notag {\Gamma'}_{\mu' \nu'}^{\lambda'} &=\frac{1}{2} {g'}^{\lambda' \rho'}(\partial_{\mu'} {g'}_{\nu' \rho'} +\partial_{\nu'} {g'}_{\rho' \mu'}-\partial_{\rho'}{g'}_{\mu' \nu'})\\ \notag&=\frac{1}{2} (\frac{\partial y ^ {\lambda'}}{\partial x^\lambda} \frac{\partial y ^ {\rho'}}{\partial x^\beta}g^{\lambda\beta})(\frac{\partial x^{\mu } }{\partial y^{\mu'} }\frac{\partial x^{\nu } }{\partial y^{\nu '} }\frac{\partial x^{\rho } }{\partial y^{\rho'}}(\partial_\mu g_{\nu \rho}+\partial_\nu g_{\rho \mu}-\partial_\rho g_{\mu \nu}) +2 g_{\nu \rho} \frac{\partial x^{\rho} }{\partial y^{\rho'} }\frac{\partial^{2} x^{\nu } }{\partial y^{\mu '}\partial y^{\nu '} })\\ \notag&=\frac{1}{2}g^{\lambda\beta}\delta_\beta^\rho \frac{\partial y ^ {\lambda'}}{\partial x^\lambda}\frac{\partial x^{\mu } }{\partial y^{\mu'} }\frac{\partial x^{\nu } }{\partial y^{\nu '}} (\partial_\mu g_{\nu \rho}+\partial_\nu g_{\rho \mu}-\partial_\rho g_{\mu \nu})+ g_{\nu \rho}g^{\lambda\beta}\delta_\beta^\rho \frac{\partial y ^ {\lambda'}}{\partial x^\lambda} \frac{\partial^{2} x^{\nu } }{\partial y^{\mu '}\partial y^{\nu '}}\\ \notag&=\frac{\partial y ^ {\lambda'}}{\partial x^\lambda}\frac{\partial x^{\mu } }{\partial y^{\mu'} }\frac{\partial x^{\nu } }{\partial y^{\nu '}} \frac{1}{2}g^{\lambda\rho}(\partial_\mu g_{\nu \rho}+\partial_\nu g_{\rho \mu}-\partial_\rho g_{\mu \nu})+\frac{\partial y ^ {\lambda'}}{\partial x^\lambda} \frac{\partial^{2} x^{\lambda } }{\partial y^{\mu '}\partial y^{\nu '}}\\ \notag&=\frac{\partial y ^ {\lambda'}}{\partial x^\lambda}\frac{\partial x^{\mu } }{\partial y^{\mu'} }\frac{\partial x^{\nu } }{\partial y^{\nu '}}\Gamma^\lambda_{\mu\nu}+\frac{\partial y ^ {\lambda'}}{\partial x^\lambda} \frac{\partial^{2} x^{\lambda } }{\partial y^{\mu '}\partial y^{\nu '}} \end{align} Thus Christoffel symbol is not a tensor.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.